Perlindungan Hukum Bagi Pihak Ketiga (Natuurlijke Persoon) Berkaitan Dengan Adanya Actio Pauliana Dalam Hukum Kepailitan - Ida Ayu Putu Purnam Asri; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Fakultas Hukum Universitas Warmadewa, 2024)
When a bankrupt debtor transfers assets to a third party, actio pauliana becomes the creditor's legal remedy to recover the assets. For good faith third parties, the application of actio pauliana in bankruptcy becomes a legal polemic. This happens because the transfer of all or part of the debtor's assets will be withdrawn through actio pauliana. So that the problem arises